Women’s Participation in Protests Against the Military Junta in Myanmar in 2021 - Lipińska, Klaudia (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
The article aims to present the events related to the coup d’état in Myanmar in 2021 and the role of women participating in the protests against this coup. The Burmese state has been struggling with many problems since its independence from the colonial rule. One of them is the continued activity of the military junta in the country’s politics. The junta ruled the country continuously from 1962 to 2011, when a democratic party took power and a civilian leader was appointed. However, the time of democracy did not last long, because on February 1, 2021, the junta staged a coup d’état and took power again. This met with discontent among the citizens, who began organizing pro-democracy protests and resisting the regime. One of the leading groups of protesters were women. They accounted for more than half of the protesters and were often the leaders of protest marches. Their high activity in protests results not only from the desire to overthrow the junta, but also from the need to fight for equality rights in a patriarchal country.